PALYNOLOGICAL CHARACTERISTICS OF THE BOTTOM SEDIMENTS OF THE SOUTHERN BARENTS SEA - Sharapova A.Yu. (My University, 2006)
The distribution of spores and pollen grains was studied in nine sections of bottom sediments up to 50 m thick, in the southern Barents Sea. The Early Cretaceous, Pleistocene, and Holocene ages of the enclosing sediments are determined by palynological analysis. Three Holocene provinces were recognized and traced along the beds, which were formed in the Early, Middle, and Late Holocene according to the scheme of Neishtadt (1957). © Pleiades Publishing, Inc. 2006.
Keywords: BARENTS SEA; HOLOCENE; PALYNOLOGICAL ANALYSIS; Cenozoic::Quaternary::Holocene; Кайнозой::Четвертичная::Голоцен